Historic Life, Interpretative Life: Hermeneutic Variations from Canguilhem’s Epistemology - Periáñez Llorente, Luis (Analysis. Journal of Philosophical Research, 2019)
In this paper we analyse the thematization that Canguilhem makes of life in its particular relation with 1) the production of value, 2) the production of signs, and 3) the production of historically developed concepts. The results aim to a reconsideration of the epistemology and history of science from the point of view of life, individuated in each case in an organism, as well as the blurring or the questioning of the radical distinction between man and animal, in dialogue with Martin Heidegger and Nietzsche. The question about that life that is already transmission of messages and history in a preconceptual sense articulates, in this way, the whole text.